Effectiveness of Using Mobile Banking Indonesian Sharia Bank - Indra Kusumawati (IAIN Palopo, 2021)
Mobile banking is a service that enables bank customers to conduct financial transactions via their mobile phones or smartphones. Mobile banking services can be accessed through menus that are already accessible via smartphone applications that customers can download and install. This study intends to describe the effectiveness of mobile banking at Bank Syariah Indonesia KCP Lombok.This study employs descriptive quantitative research with a population of all BSI KCP Lombok customers using BSI mobile banking after the 2021 merger, totaling 15,400 customers, and a sample size of 99 respondents determined using the Slovin formula. Observation, questionnaires, and documentation of BSI KCP Lombok customers who utilize BSI mobile banking were employed as research instruments. The sampling method is non-probability sampling, the data analysis method is descriptive analysis of effectiveness, and the data were processed with Microsoft Office Excel 2010 and the formula from Research and Development Dapdagri (Ministry of Home Affairs) to measure effectiveness. The findings of this study indicate that the impact of mobile banking on customer satisfaction at BSI KCP Lombok bank achieves a high level of effectiveness, as measured by R&D Dapdagri's standard table.Based on the calculation results obtained from data analysis, the percentage of each indicator in this study is 88.09%; based on standard measures of effectiveness in accordance with the standards for measuring effectiveness according to Research and Development of Dapdagri, a very effective achievement level is obtained